Plant-Produced Asialo-Erythropoietin Restores Pancreatic Beta-Cell Function by Suppressing Mammalian Sterile-20-like Kinase (MST1) and Caspase-3 Activation - Arthur, Elena; Kittur, Farooqahmed S.; Lin, Yuan; Hung, Chiu-Yueh; Sane, David C.; Xie, Jiahua (Frontiers in Pharmacology, 2017)
Pancreatic beta-cell death adversely contributes to the progression of both type I and II diabetes by undermining beta-cell mass and subsequently diminishing endogenous insulin production. Therapeutics to impede or even reverse the apoptosis and dysfunction of beta-cells are urgently needed. Asialo-rhuEPO, an enzymatically desialylated form of recombinant human erythropoietin (rhuEPO), has been shown to have cardioprotective and neuroprotective functions but with no adverse effects like that of sialylated rhuEPO. Heretofore, the anti-apoptotic effect of asialo-rhuEPO on pancreatic beta-cells has not been reported. In the current study, we investigated the cytoprotective properties of plant-produced asialo-rhuEPO (asialo-rhuEPOP) against staurosporine (STS)-induced cell death in the pancreatic beta-cell line RIN-M5F. Our results showed that 60 IU/ml asialo-rhuEPOP provided 41% cytoprotection while 60 IU/ml rhuEPO yielded no effect. Western blotting results showed that asialo-rhuEPOP treatment inhibited both MST1 and caspase-3 activation with the retention of PDX1 and insulin levels close to untreated control cells. Our study provides the first evidence indicating that asialo-rhuEPOP-mediated protection involves the reduction of MST1 activation, which is considered a key mediator of apoptotic signaling in beta-cells. Considering the many advantages its plant-based expression, asialo-rhuEPOP could be developed as a novel and inexpensive agent to treat or prevent diabetes.